ANALISIS PUTUSAN NOMOR 792/PDT.G/2018/PA.KLA TENTANG PELAKSANAAN PUTUSAN DWANGSOM DAN KONTRIBUSINYA DALAM PEMBARUAN HUKUM KELUARGA ISLAM DI INDONESIA - Oktavia, Dewi; Rofi'i, Hilmi Yusron; Qohar, Abd; Khudlori, Ahmad (UAS PRESS, 2025)
In making a decision, the Religious Court Judge should have certain considerations in deciding the hadhanah case accompanied by dwangsom. The cumulative hadhanah divorce suit accompanied by the dwangsom determination has been granted by the panel of judges in case Number 792/Pdt.G/2018/PA.Kla. This type of research is library research, namely legal research conducted by means of literature study. By using primary legal materials in the form of Decision on Case Number: 792/Pdt.G/2018/PA.Kla, secondary legal materials in the form of documents related to the research, and tertiary legal materials as a complement. Data management techniques through several stages, namely data examination (editing), data marking (coding), data reconstruction (reconstructing), and data systematization (systematizing). Based on the results of the study, it can be concluded that Decision Number: 792 / Pdt.G / 2018 / PA.Kla concerning Dwangsom in Divorce Cases of Hadhanah Compulsion Lawsuits shows that there will be a Contribution of Dwangsom as a manifestation of the values ​​of welfare and justice in the Renewal of Islamic Family Law in Indonesia. Because in cases of child custody, children as objects of lawsuits cannot be executed on the grounds that the child's position is different from property or objects. Thus, the hadhonah lawsuit accompanied by dwangsom in Decision Number: 792 / Pdt.G / 2018 / PA.Kla is an effort to prevent harm and injustice to the defendant not to hand over the child.